Association between urinary trans,trans-muconic acid and diabetes: a cross-sectional analysis of data from Korean National Environmental Health Survey (KoNEHS) cycle 3 (2015–2017) - Yang, Eun Hye; Nam, Do Jin; Lee, Hyo Choon; Shin, Soon Su; Ryoo, Jae-Hong (Annals of occupational and environmental medicine, 2021)
Benzene is a ubiquitous air pollutant that is well known to cause hematopoietic effects in humans including leukemia. Recently, several studies have discussed its non-carcinogenic effects such as diabetes. This study aimed to investigate the association between diabetes and urinary trans,trans-muconic acid (t,t-MA), one of benzene metabolite, using adult data from Korean National Environmental Health Survey (KoNEHS) cycle 3 (2015-2017). This study analyzed 3,777 adults (1,645 men and 2,132 women) from the KoNEHS cycle 3 (2015-2017). The distribution and fraction of each independent variable were presented separately according to the urinary benzene metabolite levels (t,t-MA quartiles) and diabetes to determine the general characteristics of the subjects. Odds ratios (ORs) were calculated using logistic regression after stratification by gender and smoking status to identify the association between urinary t,t-MA and diabetes. Compared with the first quartile (reference), the risk of diabetes significantly increased above the 4th (1.834 [1.107-3.039]) quartile in men and above the 3rd (1.826 [1.095-3.044]) and 4th (2.243 [1.332-3.776]) quartiles in women after adjustment. Stratified analysis based on smoking revealed that the ORs for the 3rd (1.847 [1.146-2.976]) and 4th (1.862 [1.136-3.052]) quartiles in non-smokers and those for the 2nd (1.721 [1.046-2.832]), 3rd (1.797 [1.059-3.050]), and 4th (2.546 [1.509-4.293]) quartiles in smokers were significantly higher. We confirmed that urinary t,t-MA is significantly associated with diabetes regardless of gender and smoking status. And further studies are necessary to access the clinical impacts of this findings.